Foreign student guest lecture and Indonesian EFL students' motivation in cross-culture understanding course - Imam Wahyudi Karimullah; Sari Kurnia Rahmawati; Elchin Gashimov (Journal of Research on English and Language Learning (J-REaLL), 2021)
This study explores an innovative way to increase students' learning motivation in a cross-culture understanding (CCU) class at an English Language Teaching study program in a private university in Indonesia. The lecturer assigned EFL students to find international students to share their cultures to solve students' lack of motivation in indoor learning activities. From observation, interview, and an online survey to 94 students (four classes), 98.9 % agreed that the international students' guest lecture method could increase EFL students' motivation to learn CCU. The Indonesian lecturer exposed to global culture and international students exposed to Indonesian culture becomes the primary resource for Indonesian EFL students to get insight and inspiration for their intercultural communication and adaptation practices.